Visual security defense for industrial inspection based on computer vision - Zhihao Jiang; Haotian Yuan; Chenrui Zeng; Liu Fu (PLoS ONE, 2026)
As intelligent manufacturing advances, computer vision-based defect detection systems have become essential components of industrial automation. However, this progress has also revealed new security vulnerabilities. In this work, we identify and examine a stealthy adversarial vector—the Alpha Channel Attack—which exploits the often-ignored transparency layer in RGBA images to inject imperceptible perturbations, thereby evading both human perception and conventional preprocessing defenses.We evaluate this threat across diverse model architectures, including YOLOv5, FastGAN, and state-of-the-art vision-language models such as DeepSeek-VL2, ChatGPT-4o, and KIMI. Experimental results show that alpha-channel perturbations cause substantial degradation in detection, generation, and multimodal alignment metrics—including mAP, FID, BLEU, METEOR, and CLIP Score—while leaving the visible image content unchanged.To mitigate this invisible yet high-impact risk, we propose a lightweight detection mechanism that integrates histogram overlap and MSE analysis within the alpha channel. The framework achieves an AUC of 0.998, demonstrating strong capability in identifying adversarial samples under real-world constraints.Overall, this study reveals a critical blind spot in modern visual data pipelines and introduces both a novel threat model and an effective defense strategy, contributing to the development of more resilient industrial AI systems.